Public-Private Partnership: An Effective Way to Promote Indonesian Tourism During The COVID-19 Pandemic - Aisyah, Faradiba; Sudiby, Disederius o Priyo; Nugroho, Rino Adrian (International Conference on Multidisciplinary Research, 2020)
Tourism is a sector that plays a crucial role in supporting the economy of a country. In Indonesia,tourism had significantly contributed to the increased national foreign exchange in the past few years,improving the national economy accordingly. However, the emergence of the COVID-19 pandemic inearly 2020 has hit this sector and weakened Indonesiaâ€™s economy. To improve it, the government shouldmake some innovations and involve the private sectors to achieve an optimal outcome. This publicprivatepartnership can help to solve the tourism problems since it creates a mutual relationshipbetween the public and private sectors. This research used the descriptive qualitative method andliterature study, which aimed to examine the effectiveness of PPP to be implemented by the governmentto improve the tourism industry in Indonesia during the ongoing COVID-19 pandemic. Keywords: Tourism, COVID-19, Public-Private Partnership (PPP).Â